2018
DOI: 10.1371/journal.pone.0196608
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and validation of a short French version of the Drive for Muscularity Scale in male athletes (DMS-FR)

Abstract: The purpose of this paper was to adapt and examine the psychometric properties of a French-language Drive for Muscularity Scale (DMS). First, a preliminary version of the scale, based on both the English-language version of the DMS and the literature on the drive for muscularity, was developed following a committee validation process. Second, the factor structure of the DMS-FR was investigated with principal component analysis (PCA) in a sample of 114 male athletes (Mage = 23.35; SDage = 4.93), leading to a ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…The Drive for Muscularity Scale (DMS [9];) was initially composed of two subscales: “attitudes“ and “behaviors.“ Although the DMS is the scale most often used, several limitations have been noted, such as the lack of theoretical validity and the lack of differentiation between attitudes of DM and the behaviors related to DM [42, 43]. The last version of the DMS, validated in French (DMS-FR [44];), is composed of two new subscales: “muscularity body dissatisfaction“ and “muscularity behaviors“. The five items of the Muscularity Behaviors subscale (MB; e.g., I lift weights to build up muscle ) of the French version of the Drive for Muscularity Scale ( DMS-FR [44];) were used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Drive for Muscularity Scale (DMS [9];) was initially composed of two subscales: “attitudes“ and “behaviors.“ Although the DMS is the scale most often used, several limitations have been noted, such as the lack of theoretical validity and the lack of differentiation between attitudes of DM and the behaviors related to DM [42, 43]. The last version of the DMS, validated in French (DMS-FR [44];), is composed of two new subscales: “muscularity body dissatisfaction“ and “muscularity behaviors“. The five items of the Muscularity Behaviors subscale (MB; e.g., I lift weights to build up muscle ) of the French version of the Drive for Muscularity Scale ( DMS-FR [44];) were used.…”
Section: Methodsmentioning
confidence: 99%
“…The last version of the DMS, validated in French (DMS-FR [44];), is composed of two new subscales: “muscularity body dissatisfaction“ and “muscularity behaviors“. The five items of the Muscularity Behaviors subscale (MB; e.g., I lift weights to build up muscle ) of the French version of the Drive for Muscularity Scale ( DMS-FR [44];) were used. The items were answered with a Likert scale from 1 (not at all) to 6 (absolutely).…”
Section: Methodsmentioning
confidence: 99%
“…Validated instruments are also useful for screening purposes in clinical practice. There are instruments for the measurement of a drive for muscularity like the DMS (Drive for Muscularity Scale; [ 17 , 21 ]) and instruments that aim to assess features of MD more specifically, based on Pope et al´s criteria [ 3 ]. Instruments for the assessment of MD comprise the MDSQ (Muscle Dysmorphia Symptom Questionnaire), the MASS (Muscle Appearance Satisfaction Scale), the MDQ (Muscle Dysmorphia Questionnaire), the MDI (Muscle Dysmorphic Inventory) and the MDDI (Muscle Dysmorphic Disorder Inventory; [ 22 ]).…”
Section: Introductionmentioning
confidence: 99%
“…The drive for muscularity is an individual's motivation to become more muscular (McCreary et al, 2004). Research has demonstrated that drive for muscularity is associated with the psychological distress, depressive symptoms (DeBlaere & Brewster, 2017;Eik-Nes, Austin, Blashill, Murray, & Calzo, 2018), internalized shame (Larison & Pritchard, 2019), neurotism (Benford & Swami, 2014), low self-esteem (Sepulveda, Parks, de Pellegrin, Anastasiadou, & Blanco, 2016;Swami, Barron, Lau, & Jaafar, 2016), internalization of the muscular ideals (Stratton, Donovan, Bramwell, & Loxton, 2015a), muscularity dissatisfaction (Chaba, d'Arripe-Longueville, Lentillon-Kaestner, & Scoffier-Mériaux, 2018;Liu, Chang, Gill, Wu, & Lu, 2019), difficulties in emotional regulation (Sepulveda et al, 2016), dieting and use of musclebuilding products (Eik-Nes et al, 2018), disordered eating (Arellano-Pérez, Vázquez-Cervantes, Fernández Cortés, & Saucedo-Molina, 2019;Bratland-Sanda & Sundgot-Borgen, 2012;Gomes et al, 2019;Lavender, Brown, & Murray, 2017;Liu et al, 2019), binge drinking (Eik-Nes et al, 2018) and greater hours participating in gyms (Keum, Wong, DeBlaere, & Brewster, 2015). The drive for muscularity scale (McCreary et al, 2004) is one of the main psychometrically sound measures for the exploration of the athletic/muscular -related body image (Kling et al, 2019).…”
mentioning
confidence: 99%
“…This instrument was translated into various languages demonstrating good psychometric properties. The drive for muscularity scale was validated in the samples of Asian American (Keum et al, 2015), Scottish (McPherson, McCarthy, McCreary, & McMillan, 2010), Malay (Swami et al, 2016), Romanian (Swami, Vintila, Tudorel, Goian, & Barron, 2018), Argentinian (Compte, Sepúlveda, de Pellegrin, & Blanco, 2015), Mexican (Escoto et al, 2013), French (Chaba et al, 2018), Italian (Nerini, Matera, Baroni, & Stefanile, 2016), Spanish (Sepulveda et al, 2016) samples of men. The majority of studies demonstrated good psychometric properties of the instrument (Kling, Kwakkenbos, Diedrichs, Rumsey, Frisén, et al, 2019…”
mentioning
confidence: 99%